Giant Cell Tumor (GCT) of Capitate - Narayana Gowda, BS (J Orthop Case Rep, 2012)
INTRODUCTION: Giant cell tumors (GCT) of bone are not uncommon. The most common location for this tumour is distal femur, followed by proximal tibia and distal radius (the third most common location). GCT of small bone is a rare presentation. Occurrences in the hand, however, particularly in the carpal bones are rare. We report an unusual case of GCT of Capitate in a 20 year female patient. CASE PRESENTATION: A 20 year old female patient presented with history of pain in the left wrist of 6 months duration. She was diagnosed to be having GCT of Capitate which was successfully treated with curettage, phenol ablation and bone grafting. At the end of 1 year, patient was symptom free and near normal range of movements and with no evidence of recurrence. CONCLUSION: Giant cell tumors usually are solitary lesions. Occurrence in the hand, particularly in the carpal bones is rare. This case report emphasizes the rarity of the lesion with only few cases reported in literature.